Breast cancer related PTSD in patients afer surgical treatment (mastectomy). Clinical and psychological issues - A. V. Vasileva; T. A. Karavaeva; E. P. Lukoshkina; E. E. Veiss; Ia. A. Iakovleva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Te article describes clinical and psychological issues of the PTSD development in breast cancer patients afer surgical treatment (mastectomy). Te results of comparative analysis with the use of the psychodiagnostic tests battery of the breast cancer related PTSD symptoms group and the well coped with cancer related distress group are presented. Te regression analysis results allowed to distinguish psycho-social risk factors for breast cancer related PTSD manifestation